2006
DOI: 10.1016/j.bbrc.2006.10.153
|View full text |Cite
|
Sign up to set email alerts
|

Opioid receptor-independent protection of ischemic rat hepatocytes by morphine

Abstract: We studied the role of morphine in anoxia/reoxygenation injury to hepatocytes. Overnight cultured rat hepatocytes were incubated in anoxic buffer at pH 6.2 for 4 h and reoxygenated at pH 7.4 for 2 h to simulate anoxia/reoxygenation. Some hepatocytes were preincubated with 50 μM morphine for 10 min prior to onset of anoxia/reoxygenation. To study the effect of morphine on nitric oxide (NO), hepatocytes were loaded with 4-amino-5-methylamino-2′,7′-difluorofluorescein (DAF-FM). Changes in NO concentration were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…21 A previous study using a hepatocyte anoxia/reoxygenation injury in vitro demonstrated that morphine's cytoprotective effects are independent of opioid receptor activation. 22 Nonparenchymal cells such as Kupffer cells or stellate cells are known to express opioid receptors any could also be the target cells of morphine preconditioning. Their role in in vivo hepato-protection might not be reflected in cell line studies involving only hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…21 A previous study using a hepatocyte anoxia/reoxygenation injury in vitro demonstrated that morphine's cytoprotective effects are independent of opioid receptor activation. 22 Nonparenchymal cells such as Kupffer cells or stellate cells are known to express opioid receptors any could also be the target cells of morphine preconditioning. Their role in in vivo hepato-protection might not be reflected in cell line studies involving only hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Kim and Lemasters [106] noted that in cultured rat hepatocytes, morphine improved cell viability after anoxia/reperfusion and increased NO generation, which was attenuated by ATP-sensitive K + channel blockers; however, treatment with opioid receptor antagonists did not reverse the cytoprotection conferred by morphine, indicating that morphine prevents anoxia/ reperfusion injury to hepatocytes and that the protective mechanisms may be associated with K + channels and NO, but are independent of opioid-mediated signaling.…”
Section: Digestive Systemmentioning
confidence: 94%
“…Opioid preconditioning with Tan-67 induces opioid receptor-dependent neuroprotection against ischemia in rats (1319). Opioid receptor-independent protection of ischemic rat hepatocytes was observed following morphine (581). Central and peripheral opioid receptor antagonists block the cardioprotective effects of fentanyl (649).…”
Section: B Cardioprotection and Ischemic Preconditioningmentioning
confidence: 99%